SYNTHESIS AND PHYSICOCHEMISTRY PROPERTIES PREDICTION OF A NEW POTENTIAL ANTI-INFLAMMATORY AGENT: DIACETYL PENTAGAMAVUNON-1 - Supardjan A. Margono; Pudjono Pudjono; St. Layli Prasojo; Jeffry Julianus; Enade Perdana Istyastono (Universitas Gadjah Mada, 2006)
Synthesis and physicochemistry properties prediction of a potential anti-inflammatory agent, diacetyl pentagamavunon-1 (diacetyl PGV-1), has been done. The synthesis was using pentagamavunon-1 (PGV-1) (2,87x10-3 mole) and anhydride acetic acid (26x10-3 mole; 37x10-3 mole; 49x10-3 mole) as starting materials and NaOH ethanolic as a catalyst. The AM1 semiempirical quantum-chemical calculations using the computational chemistry approach was used to predict and compare the physicochemisty properties of diacetyl PGV-1 to PGV-1. Odorless, light-yellow powder has been obtained. The powder was 0.8512-0.9602 g (2.02 x10-3 - 2.22x10-3 mole; 70.4-77.4%) and the purity of the powder was 92.4%. The purity of the product has been examined by high performance liquid chromatography (HPLC), while the structure elucidation has been done using IR (Infra Red), 1H-NMR (Nuclear Magnetic Resonance) and MS (Mass Spectroscopy). The physicochemisty properties prediction showed that diacetyl PGV-1 was more hydrophobic than PGV-1.